2004
DOI: 10.1002/cne.20249
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic relationships between axon terminals from the mediodorsal thalamic nucleus and γ‐aminobutyric acidergic cortical cells in the prelimbic cortex of the rat

Abstract: Although the reciprocal interconnections between the prefrontal cortex and the mediodorsal nucleus of the thalamus (MD) are well known, the involvement of inhibitory cortical interneurons in the neural circuit has not been fully defined. To address this issue, we conducted three combined neuroanatomical studies on the rat brain. First, the frequency and the spatial distribution of synapses made by reconstructed dendrites of nonpyramidal neurons were identified by impregnation of cortical cells with the Golgi m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…In layer IV of cat visual cortex, 2 of 31 (ϳ6%) spines contacted by a genicurocortical thalamic afferent are double innervated by a symmetrical synapse (Dehay et al, 1991). A similar result was reported in rat prefrontal cortex for afferents from the mediodorsal nucleus of the thalamus (Kuroda et al, 2004). Although their sampling number is small, together, these results suggest that only a small fraction of thalamocortical boutons form synaptic connections onto double-innervated spines.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In layer IV of cat visual cortex, 2 of 31 (ϳ6%) spines contacted by a genicurocortical thalamic afferent are double innervated by a symmetrical synapse (Dehay et al, 1991). A similar result was reported in rat prefrontal cortex for afferents from the mediodorsal nucleus of the thalamus (Kuroda et al, 2004). Although their sampling number is small, together, these results suggest that only a small fraction of thalamocortical boutons form synaptic connections onto double-innervated spines.…”
Section: Discussionsupporting
confidence: 79%
“…GABAergic synapses occur on only a minority of dendritic spines. Whether these spines are targeted by specific excitatory afferents, intracortical or thalamocortical fibers, has not yet been determined (but see Dehay et al, 1991;Kuroda et al, 2004). By reconstruction of successive ultrathin sections, we analyzed the synaptic inputs on spines in the cortex as well as the targets innervated by nonpyramidal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Kuroda also found that a low number of dendritic shafts also receive MD inputs (Kuroda et al, 1993) and that some of these targets express GABA (Kuroda et al, 2004). FFPreferential termination of thalamic afferents onto dendritic spines of pyramidal cells in other cortices has also been shown for cingulate (Vogt et al, 1981), somatosensory (Hersch and White, 1981a;Hersch and White, 1981b;Hersch and White, 1981c) or visual cortex (Peters and Saldanha, 1976c).…”
Section: Synapses Onto Spinesmentioning
confidence: 88%
“…Kuroda, in an extensive series of electron microscopic studies, described the main recipient of the MD projecting fibers as being the spines belonging to pyramidal neurons (Kuroda et al, 1996a;Kuroda et al, 1995a;Kuroda et al, 1993;Kuroda et al, 1995b;Kuroda et al, 1998a) and the dendrites of GABA local circuit neurons (Kuroda et al, 2004). However, it is still unknown if any of the GABA cell subtypes receive inputs from the MD.…”
Section: Introductionmentioning
confidence: 99%
“…The mPFC receives monosynaptic glutamatergic inputs from many brain structures including the mediodorsal thalamus (Krettek and Price, 1977;Giguere and Goldman-Rakic, 1988) and the CA1 area and subiculum of the hippocampus (Swanson, 1981;Jay and Witter, 1991;Cenquizca and Swanson, 2007;Hoover and Vertes, 2007) innervating both pyramidal cells and interneurons (Gabbott et al, 2002;Kuroda et al, 2004;Tierney et al, 2004;Rotaru et al, 2005).…”
Section: Introductionmentioning
confidence: 99%